Identification of Pedagogical Content Knowledge (PCK) for Prospective Chemistry Teachers: Efforts to Build Teachers' Professional Knowledge. Issue 1 (March 2021) - Sri, Y; Mardhiyah, A A; Mohammad, M; Endang, S
Abstract: Pedagogical content knowledge (PCK) is the basic knowledge that teachers must have to transform subject matter for students. PCK is very influential in research for teacher education, especially in science. Identification of PCK abilities needed as an effort to build teacher professional knowledge through the PCK construct. This study aims to identify the PCK ability of prospective chemistry teachers in each component. This study was descriptive with qualitative and quantitative approaches (mix-method). The instruments used in this study were the lesson plan's review sheet based on the Magnusson's framework and the interview sheets validated by two science education experts. The sampling technique was purposive sampling. The subjects of this study were 61 Chemistry Education students in the fourth semester. The identification results show that the PCK ability of prospective chemistry teachers in the components of the knowledge of curriculum, knowledge of students' understanding of science, and knowledge of assessment is still in the "fair" category with the percentage of mastery of the components respectively 70.96%; 62.70%; 74.67%. Based on the research results, it is necessary to have a professional development program to enhance the PCK ability of prospective chemistry teachers.